Hot Isostatic Pressing (HIP): A novel method to prepare Cr-doped UO2 nuclear fuel. (2020) - Cordara, Theo; Smith, Hannah; Mohun, Ritesh; Gardner, Laura J.; Stennett, Martin C.; Hyatt, Neil C.; Corkhill, Claire L.
ABSTRACT: The addition of Cr2 O3 to modern UO2 fuel modifies the microstructure so that, through the generation of larger grains during fission, a higher proportion of fission gases can be accommodated. This reduces the pellet-cladding mechanical interaction of the fuel rods, allowing the fuels to be "burned" for longer than traditional UO2 fuel, thus maximising the energy obtained. We here describe the preparation of UO2 and Cr-doped UO2 using Hot Isostatic Pressing (HIP), as a potential method for fuel fabrication, and for development of analogue materials for spent nuclear fuel research. Characterization of the synthesised materials confirmed that high density UO2 was successfully formed, and that Cr was present as particles at grain boundaries and also within the UO2 matrix, possibly in a reduced form due to the processing conditions. In contrast to studies of Cr-doped UO2 synthesised by other methods, no significant changes to the grain size were observed in the presence of Cr.